Upaya Pengelolaan Sungai Madiun Melalui Penentuan Indeks Pencemaran Air - Rizqy, Winda Nurmalia; Cundaningsih, Nurvita (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Madiun River is the largest and main river in Madiun City, which is part of the Bengawan Solo River with a river length of 141 km. Sampling was carried out at seven points along the Madiun River to determine the quality and status of the river. Parameters tested included physical (pH, TSS, DO), chemical (BOD, COD, nitrate, phosphate) and biological (faecal coliform). The Pollution Index (IP) method is used to determine the water quality status of the river, based on the Decree of the Minister of the Environment No. 115 of 2003 on the determination of water quality status. The results showed that the average IP value of the Madiun River was 2.353, which is classified as slightly polluted. The parameters BOD, phosphate and faecal coliform are the main indicators of pollution as they do not meet the requirements of Class II quality standards based on PP RI Number 22 of 2021. Reducing pollution requires routine monitoring, good management of domestic waste and socialisation of the community and farmers on the importance of maintaining river water quality. The research is expected to provide a basis for the government and stakeholders to formulate comprehensive water quality management policies and programmes.